Instrumen Tes Menggunakan Target Lingkaran Dalam Pointing Petanque - Fitri, Wulan Destiya; Dirgantoro, Edwin Wahyu; Fauzan, Lazuardy Akbar (Jurnal Porkes, 2024)
The purpose of making an instrument with this target media is to measure the potential of an athlete during the test and determine the stability of the pointing throw. Face target archery as a reference for the author who has been modified in such a way as to support the athlete's test instrument. The method used by researchers is the (R&D) method or often referred to as research and development. Researchers want to develop so that when athletes throw bosi at the target it does not change the shape of the circle and the shape of the circle the line does not disappear so it can be used many times a throw. So that researchers can conclude that the test instrument product has been tested and declared very valid by expert experts and is worth using a very good predicate. The results of the data analysis obtained by the researcher contained a product that was valid, so it was feasible to use it as a test instrument. Based on the results of the overall analysis obtained, the researcher chose to make a test instrument with this product because the instrument would be much more interesting and easier for users of athletes and coaches as well as novelty from previous research